Pemberian Konpensasi Dalam Pemanfaatan Tanah Ulayat Untuk Kepentingan Umum - Lakburlawal, Mahrita Aprilya (BAMETI Customary Law Review, 2024)
Land holds a fundamental position in community life, especially for customary law communities with spiritual and historical connections to their territories. This study examines the complex dynamics of customary land use for public purposes, focusing on compensation mechanisms and recognition fees (recognitie). There is a perspective gap between customary law communities and the government regarding the meaning of compensation: indigenous communities view it as a leasing right while maintaining management authority, while the government considers it a complete transfer of ownership. The research employs a normative juridical method to analyze legal regulations in Law Number 2 of 2012 concerning Land Acquisition for Public Interest Development. The study focuses on two primary aspects: compensation mechanisms in customary land use and the effectiveness of recognition fees (recognitie). Research results indicate that the implementation of customary land compensation still faces structural challenges. Compensation processes are often understood narrowly as a material transaction, neglecting the cultural, social, and spiritual dimensions inherent in customary land. Law Number 2 of 2012 has not fully accommodated the complexity of customary law community rights, as mandated by Article 18B of the 1945 Constitution.